Application of Ketoreductase in Asymmetric Synthesis of Pharmaceuticals and Bioactive Molecules: An Update (2018–2020). Issue 7 (9th April 2021) - Li, Zhining; Yang, Haidi; Liu, Jinyao; Huang, Zedu; Chen, Fener
Abstract: With the rapid development of genomic DNA sequencing, recombinant DNA expression, and protein engineering, biocatalysis has been increasingly and widely adopted in the synthesis of pharmaceuticals, bioactive molecules, fine chemicals, and agrochemicals. In this review, we have summarized the most recent advances achieved (2018–2020) in the research area of ketoreductase (KRED)‐catalyzed asymmetric synthesis of chiral secondary alcohol intermediates to pharmaceuticals and bioactive molecules. In the first part, synthesis of chiral alcohols with one stereocenter through the bioreduction of four different ketone classes, namely acyclic aliphatic ketones, benzyl or phenylethyl ketones, cyclic aliphatic ketones, and aryl ketones, is discussed. In the second part, KRED‐catalyzed dynamic reductive kinetic resolution and reductive desymmetrization are presented for the synthesis of chiral alcohols with two contiguous stereocenters. Abstract : This review summarizes the most recent advances achieved (2018–2020) in the research area of ketoreductase (KRED)‐catalyzed asymmetric synthesis of chiral secondary alcohol intermediates to pharmaceuticals and bioactive molecules.